Fatores extrínsecos e intrínsecos que motivam a permanência dos alunos do curso em tecnologia em hotelaria do Instituto Federal de Educação, Ciência e Tecnologia do Ceará com base na teoria da autodeterminação - Canuto, Valdiane Rodrigues (2018)
Motivation has become the target of numerous discussions in the academic context, since its absence, that is, demotivation, directly implies the quality of the students' performance in their studies. Researches, therefore, in this line, can contribute to efficiency in the teaching and learning process and identify the factors that lead to demotivation. This research is classified as quantitative and census work type, with an descritive approach, the main objective of this study is to identify the extrinsic and intrinsic factors that motivate students to stay in the Hotel Technology course at the Federal Institute of Education, Science and Technology of Ceará, based on the Self-Determination Theory developed by Deci and Ryan (1975). A total of 227 students participated in the study, with a questionnaire containing 29 sentences grouped on a Likert scale, elaborated by Guimarães and Bzuneck (2008), which were adapted from the Brazilian version of the Academic Motivation Scale (EMA) originally created by Vallerand (1989). The achieved results reveal, in a general way, that concerning to the demotivation, the students assigned the lowest grades to the items related to this factor, recording averages varying from 1.06 to 1.43 (on a scale of 4 points), which represents, in this way, a positive result. therefore, the demotivation was not noticed among the participants of this research. among the main results, it was verified that regardless of gender, income, origin of students in relation to the achievement of elementary and high school, as well as parents' scholarity, these factors do not interfere in the students’motivational aspects. the critical factors that extrinsically motivate the students are: the extrinsic motivation - introjected regulation whose average was 2.64 and the extrinsic motivation by frequency to classes which presents the average of 2.25. on the other hand, the critical factors that intrinsically motivate students are: extrinsic motivation – identified regulation with average 2.94, motivation extrinsic - integrated regulation with average 3, followed by intrinsic motivation with an average of 3.09, indicating, therefore, a more accented trend for autonomous regulation of the researched academics. As for the intention to remain in the course until its conclusion, the majority (76.3%) expressed full intention. Thus, it is expected that the results discussed may contribute to the understanding of the extrinsic and intrinsic motivational factors of the students studied, in order to stimulate them and avoid that the level of motivation decrease during the course.